Ultrasound-Guided Triamcinolone Acetonide Hydrodissection for Carpal Tunnel Syndrome: A Randomized Controlled Trial - Wang, Jia-Chi; Hsu, Po-Cheng; Wang, Kevin A.; Chang, Ke-Vin (Frontiers in Medicine, 2021)
Background: Despite the wide use of corticosteroid hydrodissection for carpal tunnel syndrome (CTS), there is insufficient evidence to confirm its efficacy. This study aimed to compare the effectiveness of corticosteroid hydrodissection vs. corticosteroid perineural injection alone on clinical and electrophysiological parameters in patients with CTS. Method: This prospective randomized controlled trial (RCT) was conducted in a tertiary care center with a follow-up period of 12 weeks. Subjects were randomly assigned to either ultrasound-guided hydrodissection with a mixture of 1 mL of triamcinolone acetonide (10 mg/mL), 1 mL of 2% lidocaine, and 8 mL normal saline or ultrasound-guided perineural injection with 1 mL of triamcinolone acetonide (40 mg/mL) and 1 mL of 2% lidocaine. The primary outcome measure was the symptom severity subscale (SSS) of Boston Carpal Tunnel Questionnaire (BCTQ) scores at baseline and at 6 and 12 weeks' post-treatment. The secondary outcomes included the functional status subscale (FSS) of BCTQ and the distal motor latency and sensory nerve conduction velocity of the median nerve. The effect of interventions on the designated outcome was analyzed using a 3 × 2 repeated measures analysis of variance. The within-subject and among-subject factors were differences in time (before the intervention, and 6 and 12 weeks after injection) and intervention types (with or without hydrodissection), respectively. Results: Sixty-four patients diagnosed with CTS were enrolled. Both groups experienced improvement in the SSS and FSS of BCTQ and median nerve distal motor latency and sensory nerve conduction velocity. However, group-by-time interactions were not significant in any outcome measurements. No serious adverse events were reported in either group, except for two patients in the hydrodissection group who reported minor post-injection pain on the first day after the intervention, which resolved spontaneously without the need for additional treatments. Conclusion: Hydrodissection did not provide an additional benefit compared to corticosteroid perineural injection alone. More prospective studies are needed to investigate the long-term effectiveness of corticosteroid hydrodissection, as well as its influence on median nerve mobility.